Revitalization of Pancasila values in building national character in the era of globalization - Amren, Hairul; Hijriayani, Wulan; Karu, Angelina Laurensia S.J; Septian, Gavrila; Bremana, Samuel; Pandiangan, Luis Obrian Christofer (EDUCTUM: Journal Research, 2026)
Pancasila, as the foundation of the state and the Indonesian nation's way of life, plays a fundamental role in shaping the nation's identity and character. However, in the era of globalization marked by technological advances, the increasingly rapid flow of information, and the strong influence of foreign cultures, the values ??of Pancasila face serious challenges in their implementation in daily life. This study aims to analyze the urgency of revitalizing Pancasila values ??in building a national character with integrity, nationalism, and personality. The method used in this study is a literature study by examining various relevant literature sources, including books, scientific journals, and government policy documents. The results of the study indicate that revitalizing Pancasila values ??needs to be carried out through character education in schools, exemplary leadership, and strengthening national culture in community life. The application of the values ??of Divinity, Humanity, Unity, Democracy, and Justice is an important foundation in facing the influence of globalization so that the Indonesian nation does not lose its moral direction and national identity. Thus, Pancasila needs to be continuously internalized contextually in every aspect of national and state life in order to realize a civilized, just, and strong-character society.